Primary Lymphoma of the Prostate: Good Outcome with Doxorubicin-Based Combination Chemotherapy - Sarris, A.; Dimopoulos, M.; Pugh, W.; Cabanillas, F. (The Journal of Urology, 1995)
Primary lymphoma of the prostate was diagnosed in 3 patients corresponding to 0.1 percent of those with previously untreated lymphoma and 0.09 percent of those with previously untreated prostatic malignancy presenting to our cancer between January 1, 1980 and December 31, 1993. All 3 patients had prostatism at presentation that caused renal failure in 2. After treatment with doxorubicin-based combination chemotherapy appropriate for the stage and the specific histological subtype, all 3 patients achieved a complete remission and remained free of disease after a minimum followup of 3 years. Our results suggest that primary prostatic lymphoma is not necessarily associated with a poor outcome. Review of the literature suggests that the poor prognosis reported for prostatic lymphoma might be explained by treatment that was acceptable at the time but would be considered suboptimal by current criteria. We recommend through staging in all patients with prostatic lymphoma and treatment with a doxorubicin-based regimen according to disease stage and histological classification. © 1995 American Urological Association, Inc.